Dr. Susan Shillinglaw
Doctor Susan Shillinglaw, as Director of the Martha Heasley Cox Center for Steinbeck Studies, speaking to group of Salinans who came to MHCCfSS for a private archival tour. The Steinbeck Center was in modular at this time. Original in safe.